2019
DOI: 10.3390/nu11122963
|View full text |Cite
|
Sign up to set email alerts
|

Fermented Korean Red Ginseng Extract Enriched in Rd and Rg3 Protects against Non-Alcoholic Fatty Liver Disease through Regulation of mTORC1

Abstract: The fermentation of Korean red ginseng (RG) increases the bioavailability and efficacy of RG, which has a protective role in various diseases. However, the ginsenoside-specific molecular mechanism of the fermented RG with Cordyceps militaris (CRG) has not been elucidated in non-alcoholic fatty liver disease (NAFLD). A mouse model of NAFLD was induced by a fast-food diet (FFD) and treated with CRG (100 or 300 mg/kg) for the last 8 weeks. CRG-mediated signaling was assessed in the liver cells isolated from mice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 61 publications
1
17
0
Order By: Relevance
“…Thus, mt-Keima enables differential imaging of mitochondria in the cytoplasm and those in acidic lysosomes [ 28 ]. To monitor the inhibition of mitophagy, we used Hep3B cells stably transfected with the mt-Keima construct where the basal level of mitophagy is relatively high [ 29 ]. High levels of acidic mitochondria were found in vehicle-treated control cells.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, mt-Keima enables differential imaging of mitochondria in the cytoplasm and those in acidic lysosomes [ 28 ]. To monitor the inhibition of mitophagy, we used Hep3B cells stably transfected with the mt-Keima construct where the basal level of mitophagy is relatively high [ 29 ]. High levels of acidic mitochondria were found in vehicle-treated control cells.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Table 3 and Figure 4 J, the saponin extract contained significantly increased amounts of several ginsenosides. Many of the upregulated ginsenosides, such as Rg1, Rg3, Rb1 [ 32 , 36 ], Rb2 [ 33 ], and Rd [ 35 ], were identified to be associated with NAFLD/NASH. In contrast, the role of Rh1 and Rg2 in hepatic pathophysiology remains unknown.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, saponin extract contained significantly increased amounts of several ginsenosides, such as Rh1 and Rg2. Although many studies have identified upregulated NAFLD/NASH-associated ginsenosides, such as Rg1, Rb1, Rg3 [ 32 , 36 ], Rd [ 35 ], and Rb2 [ 33 ], the effects of ginsenosides Rh1 and Rg2 on FFD-induced NAFLD and their potential mechanisms have not yet been explored. In the current study, the anti-inflammatory effects of saponin extract were investigated in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations